FROM ASSESSMENT TO EMPOWERMENT: QUIZIZZ AS A CATALYST FOR DIGITAL LITERACY AND INDEPENDENT LEARNING IN PRIMARY CLASSROOMS - Maryanto; Suroyo; Siti Julaeha (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The rapid advancement of information and communication technology (ICT) has transformed the landscape of education, offering new opportunities for digital and interactive learning. However, the integration of technology in learning assessment remains limited in many primary classrooms, creating a gap between pedagogical potential and actual practice. This study aims to explore how the implementation of Quizizz as a digital assessment tool can strengthen students’ digital literacy and foster independent learning. Employing a descriptive qualitative approach, data were collected from three upper-grade teachers and five students selected through purposive sampling. The data were obtained via interviews, classroom observations, and document analysis, then validated through source triangulation. Data analysis followed Miles and Huberman’s (1996) interactive model, consisting of data reduction, presentation, and conclusion drawing. The findings reveal that Quizizz enhances students’ engagement, motivation, and participation through its gamified features, point system, and instant feedback. It promotes critical and reflective thinking, helping learners develop self-regulation and confidence in using digital tools for academic purposes. Despite challenges related to device availability and internet connectivity, both teachers and students perceive Quizizz as an effective, enjoyable, and empowering platform for learning evaluation. The study concludes that integrating Quizizz not only improves digital literacy and learner autonomy but also supports the development of adaptive and creative learners prepared for digital-era education